Interrogativas-qu : um estudo introdutório comparativo a partir da hipótese da sintaxe mais simples - Pereira, André da Luz (2017)
The aim of this work is to compare syntactic approaches to wh-questions, which is based on the generative perspective developed in linguistic studies from the 1950s onwards (CHOMSKY, 1957, 1965, 1972, 1977a, 1981, 1986, 1995). The central point of the comparison is relevance of the notion of movement for the syntactic studies of wh-questions. The mainstream of generative grammar uses the notion of movement to explain syntactic phenomena, and the Simpler Syntax Hypothesis believes that this notion is unnecessary, since there would be a simpler explanation (CULICOVER; JACKENDOFF, 2005, 2006). Specifically, the explanations about the construction of wh-question structures will be compared by the Simpler Syntax Hypothesis, which presents the alternative concepts to the concept of movement to describe the phenomenon of wh-questions, such as indirect licensing and discontinuous dependencies. The idea of movement is an important axis in the mainstream generative theory, since it evolves from the theory of traces, presented in the 1970s, but which gains strength and consolidates itself as movement theory especially from the Principles and Parameters (PP) program in the 1980s. Although words such as displacement and movement have already been mentioned in the course of the generative enterprise, they are consolidated in the PP program and remain in the Minimalist Program (PM), the next stage of the generative enterprise begun in the 1990s. Another aspect identified in the development of the research was the parallel architecture of the language structure proposed by the Simpler Syntax, which challenges the central role of syntax in linguistic studies, sharing with semantics and phonology the responsibility for generating structures from Conceptual Structure. To achieve the proposed objectives, a hypothetical-deductive model was used, in which the premises proposed by the theoretical lines under study are considered. The examples and sentences analyzed were not generated in situations of use by speakers. They were extracted from the theoretical sources analyzed or generated by the author.